Upcycling expanded polyethylene waste for novel composite materials: Physico-mechanical, hygrothermal and life cycle assessment - Daniel Ferrández; Alicia Zaragoza-Benzal; Erika Barrak; Paulo Santos; Carla Rodrigues (Results in Engineering)
Recycling plastic waste is a major challenge today, but it also offers an opportunity to create sustainable building products and promote a circular economy in construction. The aim of this article is to evaluate a new lightweight plaster composite incorporating expanded polyethylene (EPE) packaging waste for lightweight steel frame (LSF) partition walls. Mechanical and hygrothermal characterization and environmental life cycle assessment are carried out on these composites with a replacement of up to 30% of the original raw material by volume. The results show that the alternative plaster has 21.7% grater flexural strength in plates than required by standards. In addition, the reduced water vapour permeability of these materials makes them more resistant to damage in high humidity environments. On the other hand, the lightened composites have 43.9% lower thermal conductivity than the reference material, increasing the thermal resistance of LSF partition walls by 20.3%. Finally, cradle-to-gate global warming potential is reduced by up to 30% compared with the 100% virgin EPE. These results are encouraging and present a significant opportunity to advance the development of sustainable novel prefabricated modular building products.